1993
DOI: 10.1002/jmv.1890400405
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐Barr virus genomic sequences and specific antibodies in cerebrospinal fluid in children with neurologic complications of acute and reactivated EBV infections

Abstract: Four children with infectious mononucleosis (IM) and one with reactivated Epstein-Barr virus (EBV) infection had concomitant central nervous system disorders. Cerebrospinal fluid (CSF) samples from all five patients contained EBV genomic sequences and EBV-specific antibodies in the neurologic stage, but not during convalescence. Cerebrospinal fluid from two non-neurologic IM patients had neither EBV DNA nor EBV antibodies. The EBV-positive CSF of the five with neurological disorders were aseptic in culture and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 31 publications
2
24
0
1
Order By: Relevance
“…The following PCR primers were used: the sense primer 5Ј-CGGTCGCCCAGTCCTACCAG-3Ј and the antisense primer 5Ј-CCTGGAGAGGTCAGGTTACT-3Ј corresponding to the Bam-HI W region of EBV based on a previous report. 33 Product size was 125 bp. The reaction conditions were as follows: denaturation at 94°C for 60 sec, annealing at 55°C for 60 sec and extension at 72°C for 120 sec.…”
Section: Analysis Of Ebv Infectionmentioning
confidence: 99%
“…The following PCR primers were used: the sense primer 5Ј-CGGTCGCCCAGTCCTACCAG-3Ј and the antisense primer 5Ј-CCTGGAGAGGTCAGGTTACT-3Ј corresponding to the Bam-HI W region of EBV based on a previous report. 33 Product size was 125 bp. The reaction conditions were as follows: denaturation at 94°C for 60 sec, annealing at 55°C for 60 sec and extension at 72°C for 120 sec.…”
Section: Analysis Of Ebv Infectionmentioning
confidence: 99%
“…In addition, acute infectious mononucleosis caused by EBV is accompanied by central nervous system disorders in 1 to 18% of patients (17,21). It was also reported that cerebrospinal fluid samples from patients with infectious mononucleosis contained EBV DNA and EBV-specific anti-VCA and anti-EA antibodies in the neurological stage but not during convalescence (26). This suggested that EBV-associated neurological complications may be due to direct virus invasion of the central nervous system, although the pathogenesis is not completely understood (13,26,76).…”
Section: Discussionmentioning
confidence: 97%
“…It was also reported that cerebrospinal fluid samples from patients with infectious mononucleosis contained EBV DNA and EBV-specific anti-VCA and anti-EA antibodies in the neurological stage but not during convalescence (26). This suggested that EBV-associated neurological complications may be due to direct virus invasion of the central nervous system, although the pathogenesis is not completely understood (13,26,76). Considering these observations together, we postulate that EBV may replicate in terminally differentiated cells or nondividing cells such as plasma B cells and neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…The primers for BamHI W region were: 3 0 -CGGTCGCCCAGTCCTACCAG-5 0 and 5 0 -CCTGGA GAGGTCAGGTTACT-3 0 . 17 The expected BamHI W region PCR product size was 125 bp. We used primers for Epstein-Barr virus nuclear antigen-4 that flank the DNA region coding for epitopes of 399-408 and 416-424 of the prototype B95.…”
Section: Eber-1 In Situ Hybridizationmentioning
confidence: 99%